The Internationalisation of fashion retailers: Zara vs. H&M Case of India - SENNAJI, Ghita / GS (2016)
According to the impressive efforts done for the improvement of policies regarding Foreign Direct Investments, the globalization of markets, the necessity of adopting high-technological tools and the willingness to satisfy existing and potential customers, companies have become involved in a panoply of international business activities in order to expand their experience and presence in the world. For that, the purpose of this dissertation is to closely and carefully analyse three different sections enrolled in the international business: the internationalization processes adopted by companies, the factors determining their decision of selecting a market, the entry modes and marketing strategies implemented for the entry.